Analysis of Local Government Information Systems on Financial Reporting Quality: Systematic Literature Review - Lala, Rona Naula Oktaviani; Nursida, Nina; Hudayati, Ataina; Arifin, Johan (Greenation Research & Yayasan Global Resarch National, 2025)
The Regional Government Information System (SIPD) plays a crucial role in enhancing the quality of financial reporting in the public sector by ensuring transparency and accountability. This study aims to identify the factors influencing SIPD implementation, explore its role in improving financial reporting quality, and examine measurement methods for related variables. The method used is a Systematic Literature Review (SLR) based on articles published between 2014 and 2024. The review results indicate that SIPD implementation is influenced by technological readiness, policy support, and human resource competencies. SIPD has been proven to enhance efficiency and accuracy in regional government financial reporting. However, challenges such as resistance to change and digital infrastructure constraints persist. This study recommends further research on integrating SIPD with emerging technologies such as artificial intelligence and blockchain to improve its effectiveness.